Multi-Electron Fused Redox Centers in Conjugated Aromatic Organic Compound as a Cathode for Rechargeable Batteries. Issue 7 (9th May 2018) - Yang, Si-Yu; Chen, Yi-Jing; Zhou, Gang; Fu, Zheng-Wen
Abstract : A conjugated aromatic compound comprising multiple fused redox centers, 5, 7, 12, 14-tetraaza-6, 13-pentacenequinone (TAPQ), is reported as an electrode of lithium-ion battery for the first time. It not only reaches a high reversible capacity but also obtains an excellent cycle ability. In addition, DFT calculations as well as FTIR, XPS and XRD analysis are performed to demonstrate the electrochemical reaction mechanism. This novel electrode can also be used in sodium and potassium batteries with a similar redox mechanism.